1986
DOI: 10.1172/jci112647
|View full text |Cite
|
Sign up to set email alerts
|

Receptor recognition of maleyl-albumin induces chemotaxis in human monocytes.

Abstract: We demonstrate here that the exceptionally active maleylalbumin receptor of human monocytes functions in vitro as a chemoattractant receptor. Chemotaxis of human monocytes occurs at an effective median dose of 34 MM maleyl-albumin, a concentration representing 1% of the total albumin in the adult human. Computerized analyses by LIGAND of the saturable binding of maleyl-albumin to human monocytes reveal two classes of binding sites, described by dissociation constants of 37 nM and 5.3 MAM with maximal binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…However, none of these agents had chemotactic activity for circulating human monocytes (data not shown). These results agree with those recently reported by Haberland et al (26).…”
Section: Methodssupporting
confidence: 94%
“…However, none of these agents had chemotactic activity for circulating human monocytes (data not shown). These results agree with those recently reported by Haberland et al (26).…”
Section: Methodssupporting
confidence: 94%
“…Unmodified BSA did not enhance any migratory activity by human monocytes. Chemotactic activity of AGE-albumin preparations was retained after extensive digestion by proteinase K (100 ;zg/mg of albumin), indicating that higher order protein structural features were not involved, as shown for albumin after maleylation (22) or single lysine glycosylation (23). Checkerboard analysis confirmed that movement of monocytes in the presence of AGEalbumin represented directed chemotaxis and not enhanced random cell migration (chemokinesis) ( Table 1): monocyte migration was enhanced only when the concentration of AGE-albumin in the lower compartment exceeded that in the upper compartment.…”
mentioning
confidence: 91%
“…In addition. mBSA interaction with its macrophage receptor{s) elicits cellular activation and chemotaxis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%